Urbanization and economic transformation: A CGE analysis for Ethiopia - Dorosh, Paul A.; Thurlow, James (International Food Policy Research Institute, 2011)
Strong economic growth in urban areas has not led to rapid urbanization in Ethiopia, possibly as a result of prevailing land tenure policies. We examine the economic implications of accelerated urbanization using a rural-urban economywide model that explicitly captures internal migration and agglomeration effects. Simulation results indicate that accelerated urbanization would strengthen economic growth, improve rural welfare, and reduce the rural-urban divide. However, without supporting investments in urban areas, the welfare gains for poorer households remain small and urban inequality worsens. At the same time, while allocating more public resources to urban areas encourages economic growth, it is less likely to benefit poor households' welfare. Indeed, even though an agriculture-oriented investment plan slows economic growth, it is more effective at improving welfare for poorer households in both rural and urban areas. We conclude that combining reforms to overcome the constraints to internal migration together with increased investment in rural areas (even at the cost of urban investment) produces outcomes most conducive to future economic development and structural transformation in Ethiopia.